2011
DOI: 10.1007/s11355-011-0153-4
|View full text |Cite
|
Sign up to set email alerts
|

The ecology of urban areas and their functions for species diversity

Abstract: Despite the appearance of an enormous number of publications about urban ecology and species diversity, many issues are simply opened up rather than explained. The ecological complexity of urban areas, i.e., the variety of determinants and the spatial and temporal dynamic of cities, preclude simple starting points and lines of explanation. Therefore, we lack sufficient comparisons between various cities, especially comparisons on a global level. If cities are to be compared by appropriate indicators, and if th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 64 publications
1
47
0
4
Order By: Relevance
“…This is not a generalized scheme among urban ecosystems (see Ricotta, Godefroid, & Rocchini, 2010), but applies to the Mediterranean ones. In any case, urban florae are primarily part of the regional pools of species (Kühn, Brandl, & Klotz, 2004;Werner, 2011;Williams et al, 2009). In Germany, Kühn et al (2004) showed that cities established in areas of high geological diversity and in preexisting biodiversity hotspots show high plant diversity as well.…”
Section: Ioannina: a Naturally Species Rich City?mentioning
confidence: 99%
See 1 more Smart Citation
“…This is not a generalized scheme among urban ecosystems (see Ricotta, Godefroid, & Rocchini, 2010), but applies to the Mediterranean ones. In any case, urban florae are primarily part of the regional pools of species (Kühn, Brandl, & Klotz, 2004;Werner, 2011;Williams et al, 2009). In Germany, Kühn et al (2004) showed that cities established in areas of high geological diversity and in preexisting biodiversity hotspots show high plant diversity as well.…”
Section: Ioannina: a Naturally Species Rich City?mentioning
confidence: 99%
“…In Mediterranean cities (Table 5), aliens' representation is generally much lower than in Central and Northern Europe because of the highly competitive native stock, which has adapted to the intense and long-standing anthropogenic disturbance (Pignatti, 1983;Werner, 2011). Aliens in Greece account only for ca.…”
Section: Aliens: Getting On or Getting By?mentioning
confidence: 99%
“…Urban habitats differ from natural, non-urban habitats in numerous ways [3]. Cities are characterized by transformed abiotic conditions, high levels of light and noise, pollution of the soil, water and air, a milder climate, later arrival of winter and earlier arrival of spring, elevated temperatures due to a high heat capacity of anthropogenic surfaces, a lower diurnal and seasonal variation in temperature, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Cities are characterized by transformed abiotic conditions, high levels of light and noise, pollution of the soil, water and air, a milder climate, later arrival of winter and earlier arrival of spring, elevated temperatures due to a high heat capacity of anthropogenic surfaces, a lower diurnal and seasonal variation in temperature, etc. [3]. Cities also offer a high availability of anthropogenic food, which-in combination with the milder climate-allows many species to extend their breeding season [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation